KEANEKARAGAMAN SPESIES LALAT DAN JENIS BAKTERI KONTAMINAN YANG DIBAWA LALAT DI RUMAH PEMOTONGAN UNGGAS (RPU) SEMARANG TAHUN 2018 DIVERSITY OF FLIES SPECIES AND TYPES OF CONTAMINANT BACTERIA BRINGING FLIES IN POULTRY CUTTING HOUSE (PCH) SEMARANG 2018 - Nanda Listya Sukmawati; Praba Ginandjar; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The existence of flies is an important public health problem. Flies are mechanical vectors, because flies can spread bacteria attached to their legs, feathers, wings and body so that flies can cause disease transmission. The purpose of this study was to determine the diversity of flies species and the type of contaminant bacteria carried by flies at the Penggaron Poultry Cutting House (PCH) in Semarang City. This type of research is an exploratory study approach by survey and laboratory examination technique, with a qualitative approach in laboratory procedures and tests. The flies that were caught 298 from the Poultry Cutting and Los Cages Kiosk consisting of Musca domestica, Sarcophagha sp and Chrysomyia megacephala were carried bacteria namely Salmonella sp, Shigella, Escherichia coli, Vibrio vulnificus, Vibrio Algimolyticus, Vibrio mimicus, Vibrio cholerae and Vibrio carchariae . The number of flies that are widely captured is Musca domestica and the most common bacteria is Escherichia coli.